Stabilizing the Imidazolium Cation in Hydroxide‐Exchange Membranes for Fuel Cells. Issue 11 (22nd August 2013) - Wang, Junhua; Gu, Shuang; Kaspar, Robert B.; Zhang, Bingzi; Yan, Yushan
<x xml:space="preserve">Abstract</x> Stable and able: The hydroxide‐conducting cationic functional group used in the hydroxide‐exchange membranes of fuel cells is key to controlling chemical stability and solubility. A new imidazolium cation, 1, 4, 5‐trimethyl‐2‐(2, 4, 6‐trimethoxyphenyl)imidazolium, is designed to take advantage of both strong electron‐donation properties and steric hindrance. Synergy between these two effects leads to an efficient hydroxide‐exchange membrane, with increased alkaline stability and improved OH− conductivity.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>